Interactive Effects of Elevated Ozone and Temperature on Growth and Yield of Soybean (Glycine max (L.) Merr.) under Field Conditions - Kent Burkey; Ripley Tisdale; Richard Zobel; Samuel Ray; Walter Pursley (Agronomy, 2020)
Elevated ozone and rising temperature are both factors in climate change, but they are difficult to study in combination due to exposure system requirements. We developed and deployed an air exclusion exposure system to treat soybean (Glycine max (L.) Merr.) cultivar “Jake” with season-long combinations of sub-ambient ozone (18 ppb, 12 h mean), elevated ozone (66 ppb, 12 h mean), and elevated temperature (+3.5 °C daytime, +2.4 °C nighttime) in irrigated field plots. Warming caused a shift in biomass partitioning from reproductive tissues into stems and petioles at mid-season that resulted in a significant 25% reduction in final seed yield and a significant reduction in harvest index. The elevated ozone treatment delayed mid-season biomass production, and final seed yield was reduced by a non-significant 2%. However, there were significant underlying effects of elevated ozone on seed production. The non-significant impact of ozone on seed yield of cultivar “Jake” resulted from significant increases in pod number (+16%) and seed number (+18%) that were offset by a significant reduction in seed size (−16%). No evidence of significant warming–ozone interactions was found in biomass or seed yield responses. In general, significant impacts of the individual warming or ozone treatments were found to be additive.